2017
DOI: 10.1155/2017/5192924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topically Administered Chitosan-N-acetylcysteine on Corneal Wound Healing in a Rabbit Model

Abstract: Purpose The present study was performed to investigate the effect of topically administered chitosan-N-acetylcysteine (C-NAC) on corneal wound healing in a rabbit model. Methods A total of 20 New Zealand White rabbits were included in the randomized, masked, placebo-controlled experiment. A monocular epithelial debridement was induced by manual scraping under general anesthesia. Animals were randomized to receive either C-NAC two times daily or placebo. Monitoring of corneal wound healing was performed with ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…The results suggested that C-NAC may impart some protective ocular surface properties [195]. Another animal clinical trial indicated that C-NAC had a positive impact on corneal wound healing [196]. Retinol palmitate is known to regulate the proliferation and differentiation of corneal epithelial cells and preserved conjunctival goblet cells.…”
Section: Other Potential Agentsmentioning
confidence: 99%
“…The results suggested that C-NAC may impart some protective ocular surface properties [195]. Another animal clinical trial indicated that C-NAC had a positive impact on corneal wound healing [196]. Retinol palmitate is known to regulate the proliferation and differentiation of corneal epithelial cells and preserved conjunctival goblet cells.…”
Section: Other Potential Agentsmentioning
confidence: 99%
“…[72]. Chitosan-N-acetylcysteine has been approved on the market as eye drops under the name Lacrimera, with increased mucoadhesive properties [73].…”
Section: Chitosanmentioning
confidence: 99%
“…B. im Rahmen eines kornealen Crosslinkings, erlaubt die UHR-OCT eine genaue Detektion der Wundränder und der Wundtiefe und damit eine präzise Vermessung der Größe des Epitheldefekts und eine Evaluierung des Heilungsverlaufs [36]. Das Gleiche gilt für präklinische korneale Wundheilungsstudien zur Beurteilung der Wirkung von epithelisierungsfördernden Substanzen [37]. Des Weiteren können durch die hoch aufgelöste Bildgebung in der Hornhaut Fälle von rezidivierenden Hornhauterosionen, z.…”
Section: Ultrahoch Aufgelöste Optische Kohärenztomografieunclassified